The de novo assembly and characterization of the complete mitochondrial genome of bottle gourd (Lagenaria siceraria) reveals the presence of homologous conformations produced by repeat-mediated recombination - Qin, Nannan; Yang, Shanjie; Wang, Yunan; Cheng, Hui; Gao, Yang; Cheng, Xiaojing; Li, Sen (Frontiers in Plant Science, 2024)
Introduction: Bottle gourd is an annual herbaceous plant that not only has high nutritional value and many medicinal applications but is also used as a rootstock for the grafting of cucurbit crops such as watermelon, cucumber and melon. Organellar genomes provide valuable resources for genetic breeding. Methods: A hybrid strategy with Illumina and Oxford Nanopore Technology sequencing data was used to assemble bottle gourd mitochondrial and chloroplast genomes. Results: The length of the bottle gourd mitochondrial genome was 357547 bp, and that of the chloroplast genome was 157121 bp. These genomes had 27 homologous fragments, accounting for 6.50% of the total length of the bottle gourd mitochondrial genome. In the mitochondrial genome, 101 simple sequence repeats (SSRs) and 10 tandem repeats were identified. Moreover, 1 pair of repeats was shown to mediate homologous recombination into 1 major conformation and 1 minor conformation. The existence of these conformations was verified via PCR amplification and Sanger sequencing. Evolutionary analysis revealed that the mitochondrial genome sequence of bottle gourd was highly conserved. Furthermore, collinearity analysis revealed many rearrangements between the homologous fragments of Cucurbita and its relatives. The Ka/Ks values for most genes were between 0.3~0.9, which means that most of the genes in the bottle gourd mitochondrial genome are under purifying selection. We also identified a total of 589 potential RNA editing sites on 38 mitochondrial protein-coding genes (PCGs) on the basis of long noncoding RNA (lncRNA)-seq data. The RNA editing sites of nad1-2, nad4L-2, atp6-718, atp9-223 and rps10-391 were successfully verified via PCR amplification and Sanger sequencing. Conclusion: In conclusion, we assembled and annotated bottle gourd mitochondrial and chloroplast genomes to provide a theoretical basis for similar organelle genomic studies.